Primary Malignant Melanoma of the Urinary Bladder - El Ammari, Jalal Eddine (Hindawi Publishing Corporation, 2011)
Introduction. Primary melanoma of the urinary bladder is very rare. As far as we know, 19 cases have been reported worldwide, usually as case reports. Case Presentation. We present a 71-year-old male patient presented with a 2-month history of hematuria. Ultrasonography revealed a 5-cm-size mass located in the bladder trigone. A transurethral resection of the bladder tumor (TURBT) revealed a malignant melanoma. Evaluation for metastatic disease was negative. The patient deceased five months later before radical treatment could be performed. Conclusion. This is one more reported case of primary melanoma of the urinary bladder. The previously reported cases of bladder melanoma are reviewed. Therapy and prognosis are discussed.